2017
DOI: 10.5039/agraria.v12i2a5439
|View full text |Cite
|
Sign up to set email alerts
|

Sprayed liquid loss due to evaporation in different psychrometric conditions

Abstract: Low relative humidity and high air temperature are favorable conditions for droplet evaporation, and this may cause financial losses for the farmer due to poor pest control, and also cause environmental contamination. Thus, the aim of this work was to evaluate the effect of temperature and relative humidity on pesticides spraying, and to estimate the spraying losses by evaporation depending on air psychrometric conditions. The experiment was carried out inside of a climate chamber to control the temperature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
(18 reference statements)
0
5
0
1
Order By: Relevance
“…Cunha et al (2016) concluded that relative air humidity was the most limiting weather element to spraying in Uberlândia, in Minas Gerais State. The presence of a high vapor pressure deficit in the air, a condition associated with low relative air humidity, may decrease the size of the droplets sprayed, making them more susceptible to wind drag (Maciel et al, 2017). Fornasiero et al (2017) established that changes in droplet size and the use of spray adjuvants are tools that can help prevent spray drift.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cunha et al (2016) concluded that relative air humidity was the most limiting weather element to spraying in Uberlândia, in Minas Gerais State. The presence of a high vapor pressure deficit in the air, a condition associated with low relative air humidity, may decrease the size of the droplets sprayed, making them more susceptible to wind drag (Maciel et al, 2017). Fornasiero et al (2017) established that changes in droplet size and the use of spray adjuvants are tools that can help prevent spray drift.…”
Section: Resultsmentioning
confidence: 99%
“…Favorability of air temperature, wind speed greater than 10 km h -1 , wind speed less than 3 km h -1 , relative air humidity, and the four conditions simultaneously (General) for agricultural spraying at different times of the day in Rio Grande do Sul State, Brazil higher (Varejão-Silva, 2006). In contrast, spray drift is strongly increased under low relative air humidity and high vapor pressure deficit (Nuyttens et al, 2006;Maciel et al, 2017). When the vertical air temperature gradient is increased, a condition that represents atmospheric instability, the convective flow may lift small spray droplets, causing them to remain longer in suspension increasing their susceptibility to the effects of wind (Fritz, 2006), which even at lower speeds can potentialize the occurrence of spray drift.…”
Section: Resultsmentioning
confidence: 99%
“…Outras pesquisas também têm evidenciado a influência da umidade relativa do ar na degradação dos princípios ativos, na deriva e na deposição dos defensivos agrícolas sobre o alvo. As menores taxas de umidade relativa do ar têm se mostrado mais propensas ao aumento da deriva e consequente redução da deposição sobre o alvo (MACIEL et al, 2017;MATTEI et al, 2019). Destaca-se, que o aumento da deriva de defensivos agrícolas pode influenciar na exposição dos trabalhadores aos agentes químicos, sendo também importante, portanto, o controle dos parâmetros meteorológicos.…”
Section: Cleonice Campos Teixeiraunclassified
“…Spray drift is a complex process that is affected by various factors, including wind speed and direction (Kruger & Antuniassi, 2019;Wang et al, 2020), air temperature (Bish et al, 2019), relative air humidity (Maciel et al, 2017), physicochemical properties of the spray solution (Liu et al, 2021), the droplet spectrum (Vieira et al, 2018), and the development stage and sensitivity of the crop (Holterman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%